2011
DOI: 10.1186/1471-2164-12-446
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing-based transcriptome analysis of Plutella xylostella larvae parasitized by Diadegma semiclausum

Abstract: BackgroundParasitoid insects manipulate their hosts' physiology by injecting various factors into their host upon parasitization. Transcriptomic approaches provide a powerful approach to study insect host-parasitoid interactions at the molecular level. In order to investigate the effects of parasitization by an ichneumonid wasp (Diadegma semiclausum) on the host (Plutella xylostella), the larval transcriptome profile was analyzed using a short-read deep sequencing method (Illumina). Symbiotic polydnaviruses (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 75 publications
(94 reference statements)
6
84
1
Order By: Relevance
“…44,47,49 In our previous RNA-seq transcriptomebased study we reported that AMPs such as gloverin, moricin, lysozyme II, and cecropin were upregulated after parasitization in P. xylostella larvae. 24 Among those antimicrobial peptides, gloverin had the highest transcription levels, which suggests that following parasitoid attack by suppression of miR-8 and its target Serpin 27 gloverin gene expression is activated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…44,47,49 In our previous RNA-seq transcriptomebased study we reported that AMPs such as gloverin, moricin, lysozyme II, and cecropin were upregulated after parasitization in P. xylostella larvae. 24 Among those antimicrobial peptides, gloverin had the highest transcription levels, which suggests that following parasitoid attack by suppression of miR-8 and its target Serpin 27 gloverin gene expression is activated.…”
Section: Discussionmentioning
confidence: 98%
“…[21][22][23] Several studies have shown that parasitic wasps have significant effects on host metabolism and development through interruption of host gene transcription, immune pathways, nutrition, and endocrine systems, and even regulate miRNA levels. 18,[24][25][26][27][28][29] Therefore, endoparasitoid wasps provide ideal biological tools to study the basic mechanisms underlying insect immune responses due to their profound impact on the host immune system.…”
Section: Conserved Microrna Mir-8 Blocks Activation Of the Toll Pathwmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only two other high-throughput transcriptomic approaches have been conducted on similar host-parasitoid systems involving DsIV and CchBV; in each case, the expressions of only 19 viral genes from 5 and 6 gene families, respectively, were detected (30,31). Even if the reference genomes are not available for these viruses, the expression of a larger number of genes might have been expected, considering the number of genes predicted in related viruses (19,23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deep sequencing approaches at the transcriptome level concerned the expression of the Diadegma semiclausum ichnovirus (DsIV) in Plutella xylostella larvae and the expression of Cotesia chilonis bracovirus (CchBV) in the Chilo suppressalis host. In these de novo transcriptomic approaches applied to new model species, the relative contributions of IV and BV gene expression could not be evaluated because the genomes of these PDVs have not yet been sequenced (30,31).…”
Section: Importancementioning
confidence: 99%